Constructing Useful Models of Firms’ Heterogeneities in Implemented Strategies and Performance Outcomes - Brenes, E.; Ciravegna, L.; Woodside, Arch (Elsevier, 2017)
This study advances the proposition that applying core tenets of complexity theory is useful for solving the “crucial problem” in strategic management—describing, explaining, and predicting firm heterogeneity. The study describes the core tenets (e.g., the necessity of constructing models for cases with relationship reversals to a significant main effect—cases occur whereby both high and low scores of an antecedent condition indicate high scores in an outcome condition; asymmetric models are necessary because the causes of successful outcomes are not the mirror opposite of the causes of unsuccessful outcomes). Constructing “somewhat precise outcomes models” (SPOM) rather than null hypothesis statistical testing (NHST) is the principal analytic tool. The study describes asymmetric models of implemented strategy and competitive advantage for ROE, negation of ROE, and complex outcome statements for agribusiness firms (n = 247) across seven Latin America national as well as tests the predictive validities of models across specific nations for the models of sampled firms within Costa Rica, El Salvador, Guatemala, and Nicaragua. The findings support the propositions that constructing complex antecedent statements (i.e., algorithms/configurations/recipes/screens) are useful for indicating high performance or the negation of high performance consistently. Configural implemented strategy models have direct influences on both high and low performance outcomes, while competitive advantage models impact low, but not, high performance outcomes. Complex competitive advantage conditions contribute indirectly to high performance outcomes.